Real-Time Monitoring of the Dehydrogenation Behavior of a Mg2FeH6-MgH2 Composite by In Situ Transmission Electron Microscopy - Kim, Juyoung; Fadonougbo, Julien O.; Bae, Jee Hwan; Cho, Min Kyung; Hong, Jaeyoung; Cho, Young Whan; Roh, Jong Wook; Kim, Gyeung Ho; Han, Jun Hyun; Lee, Young-Su; Cho, Jung Young; Lee, Kyu Hyoung; et al. (John Wiley & Sons Ltd., 2022)
Herein, real-time observations of dehydrogenation of a Mg2FeH6-MgH2 composite by means of in situ transmission electron microscopy (TEM) with advanced spatial (approximate to 0.8 angstrom) and temporal (25 frames s(-1)) resolution are reported. Careful control and systematic variations of the reaction temperature and electron dose rate enable detailed and direct visualization of the characteristic decomposition of Mg2FeH6 into Mg and Fe, which occurs on the nanometer scale under optimal experimental conditions defined to minimize the electron-beam-driven Mg oxidation and dehydrogenation that take place in TEM. First, the formation of nanostructured fine Fe clusters in Mg metal and their growth via coalescence during dehydrogenation are verified. Additionally, fine monitoring of the in situ diffraction patterns acquired during decomposition of the composite allows separate evaluations of the desorption kinetics of the two coexisting phases, which confirm the synergetic dehydrogenation of this dual-phase system. It is envisioned that these findings will provide useful guidelines for reducing the gaps between nanoscale and bulk-scale research and designing hydrogen sorption conditions to enable efficient operation of a solid-state hydrogen storage system.